Increased risk of acute coronary syndrome among patients with urinary stone disease: a nationwide population-based cohort study. - Shun-Fa Hung; Chao-Yuan Huang; Cheng-Li Lin; Shiu-Dong Chung; Chi-Jung Chung; Chia-Hung Kao; Chao-Hsiang Chang (PLoS ONE, 2014)
Urinary stones (US) are associated with systemic metabolic and endocrine disorders that share risk factors typically associated with acute coronary syndrome (ACS).For this investigation, 30,142 patients with US were set as the research group, and 121,768 randomly selected patients were set as the comparison group through frequency matching by age, sex, and index year. Each patient was individually tracked to identify those who developed ACS during the follow-up period. Cox proportional hazards regression and the Kaplan-Meier method were adopted to calculate the hazard ratios of ACS risk and plot the survival curve.Overall, 275 (13.4 per 10,000 person-y) and 736 events (9.1 per 10,000 person-y) were observed among patients in the research and comparison cohorts, respectively. The patients with US had a substantially lower ACS-free survival rate compared with that of the patients in the comparison cohort (P<.001). After adjusting for potential risk factors, the patients with US were observed to have a 1.22-fold higher risk of ACS compared with patients in the comparison cohort (95% confidence interval = 1.05-1.40, P<.001), particularly among younger patients.The results indicate that US is associated with increased risk of developing ACS, particularly among young (≤ 49 years) and male adults. Future studies should examine the possible mechanisms of US-related ACS morbidity by conducting multicenter recruitment and measurements of laboratory data.